Demystifying the potency of marketing strategies as a tool for creating competitive advantage in challenging times - Steven Kayambazinthu Msosa; Thembisa Charity Khuboni; Siyabonga Maphumulo; Bhekabantu Alson Ntshangase (Insights into Regional Development, 2024)
The COVID-19 pandemic has caused unexpected shocks to several sectors of the economy, including the insurance industry. The devastating effects of the pandemic have also affected the marketing model and the strategies' effectiveness. Therefore, this study sought to demystify the potency of marketing strategies as a tool for achieving competitive advantage in challenging times. An exploratory and qualitative research design was used to gain in-depth insight into the motivations and perceptions of a purposive sample of 15 insurance customers. Thus, interviews were conducted to gather data to determine the potency of the marketing strategies. The research findings showed that different companies used various marketing strategies, resulting in varying customer satisfaction. Some companies used low-cost strategies, while others focused on product differentiation strategies. It was further found that most customers prefer a lower price and reliable service from trustworthy insurers. In addition, it was noted that companies with high customer satisfaction levels outperformed their competitors and achieved a competitive advantage in the short-term insurance sector. This sector is customer-centric, so a higher emphasis must be placed on delivering quality service and customer satisfaction. Consequently, companies in the insurance sector will be able to keep customers satisfied over long periods and ultimately achieve customer loyalty. The study elucidates the pathway for insurance companies to navigate challenging times successfully by focusing on delivering quality service and nurturing customer satisfaction for long-term loyalty.